Konstruksi Sosial terhadap Risiko Lingkungan dan Implikasinya terhadap Partisipasi Publik dalam Perencanaan Pembangunan Berkelanjutan - Hidayah S, Syaiful; Umar, Genius (PT Hakhara Akademia Indonesia, 2025)
This study examines the social construction of environmental risks and their implications for public participation in sustainable development planning. development that often has negative impacts on the environment, perceptions and communities towards risks play a role in determining their level of participation. Through a qualitative approach with literature studies and document analysis, this study found that environmental risk perceptions are not only shaped by scientific knowledge, but also by social values, culture, collective experiences, and access to information. When communities view environmental risks as real threats to their lives, participation in the planning process tends to increase. Conversely, if risks are considered abstract or manipulated by certain interests, participation becomes low. These findings indicate the importance of open dialogue between the government, development actors, and communities to build together. Social construction of environmental risks plays a strategic role in shaping collective action and the direction of more inclusive and sustainable development.